Program for correction of excessive weight in children during physical education classes at school (Bangladesh Journal of Medical Science, 2026)
Aim is to improve the physical development and physical fitness of primary school children who are overweight through physical education. Materials and methods The study was conducted from January to May 2024 at the comprehensive school in Moscow (Russia). The pedagogical experiment involved schoolchildren who study in grades 1-4 who were diagnosed with obesity of varying degrees (72 children). Children in the experimental group did physical education with a separate instructor according to the experimental program, and schoolchildren from the control group studied in one with the rest of their class. Before and after the pedagogical experiment, all schoolchildren completed control tests that assessed their level of physical development and physical fitness. Results During the study period, the schoolchildren from the control group showed an increase in the indicators of less than 2% in the EVC, Height, Weight, BMI, Jump and Run tests (p> 0.05). In the RI test, the indicators improved from 10.3±1.6 to 9.4±0.65 (t=0.52; p>0.05), the increase was 9.6%. In the Torso test, the indicators improved by 11.5% (p> 0.05), and in the Jump Rope test, the result was higher by 14.6% (p> 0.05). In the experimental group, a reliable increase in the results was recorded in 7 of 9 tests. The smallest increase in results was noted in the Height test - 1.1% (p>0.05) and Run - 0.6% p>0.05. The EVC increased by 14.2% (p